Kontribusi Tafsir al-Azhar Terhadap Nilai-Nilai Pendidikan Islam (Kajian QS al-Isra’ ayat 22-39) - Yunita, Nurma (Institut Agama Islam Negeri (IAIN) Curup, 2017)
This article aims to investigate the values of education contained in Surah al-Isra' verse 22-39 by Hamka’s interpretation in the interpretation of al-Azhar. This study is a qualitative research as content analysis. The data obtained and analyzed by the method of content analysis. The interpretation of al-Azhar contributes to the values of education, it can be seen from the values of Islam from the education that is contained in the commentary of al-Azhar in Surah Al-Isra' verse 22-39, namely: (1) The educational value of faith: Tauhid, repentance, resignation, sincere, grateful, steer clear of adultery, low self-esteem, piety and charity with knowledge. (2) The value of social education: Respect, affection and mutual help. (3) The educational value of Virtue: Generous, simple, keeping promises, patient and honest.